Chlorination Kinetics of Xenotime with Chlorine in Presence of Carbon - M. A. Gimenes (The Minerals, Metals and Materials Society, 2000)
The utilization of chlorination in extractive metallurgy and advanced ceramics areas has been widely investigated as a preparative route in order to obtain intermetallic compounds, which are used as precursors in the development of new materials and process. The major processes of decomposition of rare-earth ores use sulfuric acid and sodium hydroxide at high temperatures, however there is not much work concerning chlorination. In this work, a systematic study of the reaction between xenotime (REPO4), chlorine and carbon has been performed. Particular emphasis was on kinetic studies to establish optimized conditions for the reaction. The kinetics of chlorination of xenotime raw material by rare-earth elements/compounds has been studied over a temperature range from 600°C to 950°C. The influence on the rate of conversion of xenotime to RECl3 on temperature, partial pressure of chlorine, carbon content, and particle size were investigated. A global rate equation that includes these parameters has been developed. The results show that the process follows the unreacted core-shrinking model with a formation of a porous product layer. The powder X ray-diffraction technique corroborated this model showing clearly the patterns related to the formation of yttrium oxychloride (YOCl), indicating that the reaction mechanism involves the presence ofan intermediate step before the formation of lanthanide chloride.